Effect of vgb gene on microbial chondroitin sulfate production in recombinant Escherichia coli pETM6-PACF-vgb and physicochemical characterization of produced chondroitin sulfate: Effect of vgb on microbial chondroitin sulfate production - Erenler, Ayse Sebnem; Unver, Tuba; Ceylan, Ahmet Faruk; Ozcan, Imren; Geckil, Hikmet (Cellular and Molecular Biology, 2025)
Chondroitin Sulfate (CS) is an essential component of the extracellular matrix and is a sulfated glycosaminoglycan structurally composed of a polysaccharide chain consisting of N-acetyl galactosamine and glucuronic acid. The use of CS of animal origin is common in pharmacological research. The disadvantages of traditional sources and methods used in the production of CS, which is used in various applications in the medicine, veterinary, pharmacy, and cosmetic sectors, have made microbial production a vital alternative. In this study, recombinant Escherichia coli (pETM6-PACF-vgb) strain, in which kfoA, kfoC, kfoF and vgb gene regions are co-expressed, and E. coli pETM6-PACF strain, which does not contain the vgb gene, were used in the microbial production of CS. The vgb gene is the region responsible for expressing the bacterial protein Vitreoscilla hemoglobin (VtHb). This study investigated the effect of the expression of VtHb in E. coli on increasing bacterial cell respiration and, therefore, how ATP production would affect cell growth and the acquisition of chondroitin and microbial chondroitin sulfate (MCS) from biomass. The analysis results determined a 23.07% increase in the amount of MCS produced from the vgb+ strain. The presence of vgb had positively affected culture age and reproductive kinetics. Spectrophotometric measurements, NMR, HPLC, FT-IR, TGA, DTA, and DSC analyses for the reproductive values ​​and physicochemical characterization of the obtained MCS were applied to discuss this production process. For more detailed results on this subject, future research focused on optimization is needed.